Marketing on the Move: From Traditional to Greener Making Coherent for the Friendly Environment - Shrivastava, Ajit; Rai , Shivam (Gyan Management Journal, 2018)
The purpose of this paper is to determine the development of the definition of green marketing, problems, the role of marketers and consumer behaviour towards green marketing. This paper provides a conceptual method of green marketing by conducting a literature study of research on green marching. The result can be concluded that marketers have two roles, namely as creators of behaviour change by providing green products and education. And the second marketer as a search for factors that influence consumers in buying green products. This is done by marketers because the market has not been created and marketers still do not understand the black box of consumers towards. This minimization is possibly the most essential social responsibility of the enterprises. In order to fulfil this, they ought to undertake environmental pleasant policies in the manufacturing administration and consist of environmental problems in their manufacturing functions. Newly, environmental sensitivity has been growing quickly. Business uses clean production technological know-how as for proving whose environmental sensitivity and responding their client demands. For this reason, market research, enchantment of marketing strategies has to be accomplished and the shoppers are knowledgeable and satisfied about the surroundings protective products. Green marketing is an activity designed to generate and facilitate various changes to obtain satisfaction from what is desired and needed by humans, by minimizing the effects that damage the environment. Green marketing is very important because of the limited availability of natural resources. One product that consumers constantly use is electricity. Most consumers are willing to pay more to get environmentally friendly renewable energy. This is evidenced by a study in the United States about increasing customer demand for renewable energy. Both green marketing and products made from environment-friendly materials are well recommended by experts who believe that such exercise controls the pandemic impact on nature.